Point prevalence of chronic wounds at a tertiary hospital in Nigeria (2016)
Abstract: Background. Chronic wounds are a drain on resources both for the patient and health institution. Management of chronic wounds based on evidence-based practice requires baseline data for adequate planning. Objectives. This study was carried out to determine the point prevalence of chronic wounds in a tertiary hospital (University College Hospital, Ibadan, Nigeria) and utilize this information for subsequent wound care planning. Methods. The study was carried out within a 1-month period and included all patients seen in the hospital with chronic wounds. The data obtained was entered into a designed form and was subsequently analyzed. Results. There were 48 patients with 78 wounds representing approximately 11% of patients seen in the Department of Plastic, Reconstructive, and Aesthetic Surgery each month. Their ages ranged from 3 months to 80 years; the median age was 48 years. The male to female ratio was 1.6 to 1. The duration of the wounds ranged from 6 weeks to 780 weeks; the median duration of the wounds was 10 weeks. The area of the wounds ranged from 1 cm2 -1,248 cm2 (median 24 cm2). The most common chronic wounds were diabetic wounds, followed by pressure ulcers, postinfection ulcers, posttraumatic ulcers, burn wounds, malignant ulcers, and venous ulcers. Conclusion. The point prevalence data serves as a basis for wound care planning. This, in turn, should result in improved wound management grounded in evidence-based practices.